Mengenal Media Promosi Konvensional Sebagai Sarana Penyebaran Informasi Mengenai Destinasi Wisata Kedunglumpang Pangandaran - Khadijah, Ute Lies Siti; Rizal, Edwin; Hadian, Sapari Dwi; Khoerunnisa, Lutfi (Jurnal Ilmiah Pariwisata, 2021)
In the midst of the current modern globalization, the use of social media has almost been enjoyed by most people. However, it turns out that not all elements of society have the ability to use social media. The existence of this conventional media is still sustainable and is used today, in fact it is still a favorite media for villagers in Kedungwuluh, Pangandaran. The method used in this research is a qualitative descriptive method, in which the writer tries to describe in detail and detail a certain phenomenon. This study emphasizes the development of concepts and collects facts found in the field and does not carry out hypotheses. The purpose of this study was to determine the reasons for tourism managers and local village officials to maintain this conventional promotional media as one of the important media in promoting Kedung Lumpang tourism. The next goal is to find out what conventional media are used in the promotion. The result of this research is that there are several conventional media which are considered effective in the current promotion process. First, through word of mouth. The second is through parades or mobile announcements, and the last is through a carnival. Keywords: Conventional promotion media, Kedung Lumpang tourism, Public information, Rural communities